Child Criminality Under Algorithmic Colonization for Digital Existence - Zainal Arifin Hoesein; Beby Savitri; Alfin Suherman (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid development of technology has trapped children within the vortex of social media algorithms that encourage criminal acts in pursuit of digital existence. This study aims to analyze the philosophical roots of the shifting legal awareness of children through a confrontation between Jeremy Bentham’s theory of Utilitarianism and Jean Baudrillard’s theory of Hyperreality. Employing a doctrinal legal research method with conceptual and legal philosophical approaches, this article examines how social media algorithms based on the competition for public attention have created a space of simulacra. Within Baudrillard’s condition of hyperreality, children live in an artificial reality that is perceived as more real than the physical world, causing moral and legal boundaries to become blurred. This condition ultimately distorts Bentham’s hedonistic calculus within children; the desire to seek pleasure in the form of instant validation, likes, and digital recognition surpasses their rational awareness of pain in the form of threats of criminal sanctions. This study concludes that child criminality in the digital era is not merely a violation of conventional legal norms but rather a consequence of the “colonization” of algorithms that weakens children’s normative legal awareness. This philosophical understanding is essential as an initial foundation in formulating future directions for regulatory reform on child protection and legal education.